The impact of the COVID-19 pandemic on financial report MSMES business practices: A phenomenological analysis - Harun Alrasyid; Abdul Malik; Sultan Sultan (Universitas Pendidikan Nasional, 2023)
This study delved into the repercussions of the COVID-19 pandemic on the Financial Statements and Business Practices of Micro, Small, and Medium Enterprises (MSMEs) in Palopo City. Utilizing a qualitative phenomenological approach within an interpretive paradigm, the study involved 3 business owners, 1 consumer, and 1 government representative as informants. Data collection methods included interviews, observation, and documentation. The interactive data analysis method, encompassing data reduction, presentation, conclusion, and verification, was employed. The findings indicated a profound impact of the COVID-19 pandemic on the financial reports and business practices of MSMEs. There was a substantial reduction in turnover across various MSME sectors, particularly affecting wholesale and retail traders, food and beverage, and tourism. According to LIPI's P2E data, micro food and beverage businesses experienced a 27% impact, small businesses at 1.77%, and medium-sized businesses at 0.07%. The study highlighted the pandemic's effects on MSMEs, including decreased sales, income reduction, employee cuts, weakened purchasing power, and increased expenditures.